2019
DOI: 10.1101/673871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novelty gates memory formation through ventro-dorsal hippocampal interaction

Abstract: Novelty facilitates formation of memories. The detection of novelty and storage of contextual memories are both mediated by the hippocampus, yet the mechanisms that link these two functions remain to be defined. Dentate granule cells (GCs) of the dorsal hippocampus fire upon novelty exposure forming engrams of contextual memory. However, their key excitatory inputs from the entorhinal cortex are not responsive to novelty and are insufficient to make dorsal GCs fire reliably. Here we uncover a powerful glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…As sections progressed to more caudal and ventral regions, the number of GFP hilar cells increased significantly ( Figure 3B5-B10). A very small number of weakly-labeled GFP cells were observed in the CA3c region of some sections ( Figure 3B7-B9), consistent with previous reports (Fredes et al, 2019;Yeh et al, 2018). Importantly, the GFP axon was largely restricted to the IML of the DG throughout the entire septotemporal axis of the DG.…”
Section: Coronal Sectionssupporting
confidence: 90%
See 1 more Smart Citation
“…As sections progressed to more caudal and ventral regions, the number of GFP hilar cells increased significantly ( Figure 3B5-B10). A very small number of weakly-labeled GFP cells were observed in the CA3c region of some sections ( Figure 3B7-B9), consistent with previous reports (Fredes et al, 2019;Yeh et al, 2018). Importantly, the GFP axon was largely restricted to the IML of the DG throughout the entire septotemporal axis of the DG.…”
Section: Coronal Sectionssupporting
confidence: 90%
“…Another study which suggested that dorsal and ventral MCs were different was electrophysiological, and used hippocampal slices to show that ventral MCs exhibited a greater degree of bursts in response to pharmacological agents (Jinno et al, 2003). More recently, a study in transgenic mice showed that ventral MCs have significantly different effects on behavior compared to dorsal MCs (Fredes et al, 2019).…”
Section: Differences Between Dorsal and Ventral Mcsmentioning
confidence: 99%
“…Interestingly, dMCs are enriched in a subset of synaptic regulators, including Epha7 and Nrg3, that are known to promote the excitatory synaptogenesis onto PV + BCs in the hippocampus 27,28 . Indeed, a recent study using electron microscopy showed that dMCs innervate PV + BC dendrites to a much higher extent than vMCs do 17 . It also reported that vMCs have a net excitatory effect on GCs in a novel environment, although we could not observe similar effect in our CFC paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy studies showed that the axonal arborizations of MCs in the IML of the DG make direct synaptic connections with proximal dendrites of GCs and also of GABAergic interneurons 12,16 . Genetic ablation of whole MCs results in transient hyperexcitability of GCs 8 , whereas chemogenetic activation of MCs exert an excitatory effect on GCs 17 , suggesting considerable inconsistency in the net effect of MCs on GCs. Considering the functional heterogeneity of the hippocampus, it is plausible that MCs consist of multiple subpopulations with distinct properties and functions.…”
Section: Introductionmentioning
confidence: 99%
“…Less attention has been devoted to the role of MCs, especially vMCs, in behavior relevant to neuropsychiatric disease including learning, memory, novelty, and anxiety, however there is growing research interest in these topics. Distinctions between vMCs and dMCs are supported by physiological [72][73][74][75], biochemical [29,30], and anatomical [75][76][77] evidence. It thus may not be sufficient to extrapolate findings from dMCs to all MCs across the HPC longitudinal axis.…”
Section: Discussionmentioning
confidence: 99%